Clinical efficacy of adaptive biofeedback training combined with oral administration of compound polyethylene glycol 4000-electrolyte powder in the treatment of children with outlet obstruction constipation: a prospective randomized controlled trial - Wang, Rui-Feng; Zhou, Fang; Wang, Huan; Yu, Zhi-Dan; Li, Xiao-Qin (Zhongguo dang dai er ke za zhi, 2022)
To study the clinical efficacy, advantages, and disadvantages of adaptive biofeedback training combined with oral administration of compound polyethylene glycol 4000-electrolyte powder in the treatment of children with outlet obstruction constipation (OOC). A total of 168 children with OOC were enrolled in this prospective study. All the subjects were randomly divided into a test group and a control group based on the order of visiting time, 84 in each group. The test group was treated with adaptive biofeedback training combined with oral administration of compound polyethylene glycol 4000-electrolyte powder, and the control group was treated with oral administration of compound polyethylene glycol 4000-electrolyte powder alone. Eleven children in the test group and two children in the control group withdrew from the study since they could not finish the whole treatment course. Finally, 73 children in the test group and 82 children in the control group were included in this analysis. As clinical outcomes, the